Tudy on Achievement Test of Students and Role of Teacher: Exploring the Efficacy of Teacher-Created Achievement Tests (Journal of Advances and Scholarly Researches in Allied Education, 2012)
These tests are prepared by the teachers themselves.These tests are quite refined and objective.